CONGENITAL VARICELLA SYNDROME: A SYSTEMATIC REVIEW - Tegar Perbawa, Prayudha (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Herpes viruses are extremely infectious, and the varicella-zoster virus (VZV) is one of the most contagious. Because the varicella vaccination was made available to all children in the United States (US) and Europe in 1995, the vast majority of adults in these regions are immune. It is believed that more than 90 percent of the prenatal population have VZV IgG antibodies, and as a result, is resistant to illness caused by the virus. The woman had a history of varicella before to the beginning of her pregnancy, which lasted the first three months of her pregnancy. Manifestations in newborns can start as early as a few weeks before delivery and can continue for up to a month after birth. Manifestations can begin as early as a few weeks before delivery. A centripetal rash, which begins on the trunk and spreads to the face and limbs, is one of the clinical signs that can be seen on the skin. This rash begins with erythematous macules, then progresses to vesicles, and finally ruptures to form crusts. In order to establish a diagnosis of varicella, medical professionals look to the clinical signs of the disease on the skin. On the other hand, there is always the opportunity to carry out more research. If a pregnant woman contracts varicella at any point throughout her pregnancy, at term, or in the immediate postpartum period, it has the potential to cause substantial morbidity in the newborn offspring of that woman. Varicella congenital syndrome can result in serious birth malformations such as hypoplasia of an extremity, microcephaly, abnormalities of the skin and eyes, intellectual impairment, and low birth weight.